SAW ANALYSIS DETERMINATION OF MICRO BUSINESS CREDIT RECIPIENTS AT DISKOPDAGIN - Amanda, Siska; Fauziah, Rizky; Apridonal, Yori (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2023)
Abstract : In building community economic independence, each year DISKOPDAGIN provides micro business loans sourced from the Asahan Regency Regional Revenue and Expenditure Budget (APBD) funds which aim to help strengthen capital for micro business actors. However, in providing micro business credit, certain conditions or criteria are required so that the DISKOPDAGIN can determine whether the customer receiving the micro business loan is eligible to receive credit or not. The problem that is often faced by the Department of Industry and Trade at this time is the difficulty in making decisions to determine recipients of micro business loans. The purpose of this research is to facilitate the Department of Industry and Trade in selecting micro business credit customers. The Simple Additive Weighting (SAW) method in this study aims to select the best alternative from a number of alternatives to be used based on specified criteria. The results of this study are micro business credit decision support systems, where the application of this system shows that the results of the ranking process with the SAW method are the same if calculated manually. The calculation uses 7 criteria where the highest alternative is the Asmah alternative (A7) with a preference value of 1. Keywords: decision support system; micro business credit; simple additive weighting; Abstrak: Dalam membangun kemandirian ekonomi masyarakat, tiap tahunnya DISKOPDAGIN mengadakan kredit usaha mikro yang bersumber dari dana Anggaran Pendapatan dan Belanja Daerah (APBD) Kabupaten Asahan yang bertujuan untuk membantu penguatan modal kepada pelaku usaha mikro. Namun dalam memberikan kredit usaha mikro juga mempunyai syarat-syarat atau kriteria tertentu agar pihak DISKOPDAGIN dapat menentukan apakah nasabah penerima kredit usaha mikro tersebut layak menerima kredit atau tidak. Permasalahan yang sering dihadapi oleh pihak DISPERINDAG saat ini ialah kesulitan dalam mengambil keputusan untuk menentukan penerima kredit usaha mikro. Tujuan dari penelitian ini untuk memudahkan pihak DISPERINDAG dalam menyeleksi nasabah kredit usaha mikro. Metode Simple Additive Weighting (SAW) dalam penelitian ini bertujuan untuk menyeleksi alternatif terbaik dari sejumlah alternatif yang akan digunakan berdasarkan kriteri yang ditentukan. Hasil penelitian ini sistem pendukung keputusan kredit usaha mikro, dimana penerapan sistem ini menunjukkan bahwa hasil dari proses perangkingan dengan metode SAW sama jika dihitung secara manual. Perhitungan menggunakan 7 kriteria dimana alternatif yang tertinggi adalah alternatif Asmah (A7) dengan nilai preferensi 1.Kata Kunci: kredit usaha mikro; sistem pendukung keputusan; simple additive weighting;